Calculation of electromotive force (EMF) on hybrid ignition systems - Do, Quốc Ấm; Do , Văn Dũng; Phan, Nguyễn Quí Tâm; Le, Khánh Tân (Journal of Technical Education Science, 2015)
This paper presents a computing method of the electromotive force on hybrid ignition system which combines capacitor discharged and inductance ignitions. Evaluate these calculations. The results have defined the oscillating pattern of waveforms and the parameters that influenced on performance of hybrid ignition systems.